Variations in the Functional Diversity of Rhizosphere Microbiome of Healthy and Northern Corn Leaf Blight Infected Maize (Zea mays L.) - Dlamini, Siphiwe Prudence; Akanmu, Akinlolu Olalekan; Babalola, Olubukola Oluranti (Spanish Journal of Soil Science, 2023)
Metagenomics is a scientific breakthrough that can reveal the variations in the microbial diversities and functions between the healthy and diseased plants, towards a productive deployment in diverse biotechnological processes and agricultural activities. This study investigated the possible functional diversity in the rhizosphere microbiome of both healthy and Northern Corn Leaf Blight (NCLB) infected maize growing at farms in the Lichtenburg (LI) and Mafikeng (MA) areas of the North West Province, South Africa. We hypothesized variations in the abundance and diversities of microbial functions in the healthy (LI and MA) and diseased (LID and MAD) maize plants. Hence, we extracted DNA from the healthy and diseased maize rhizosphere in the two maize farms and sequenced using a shotgun approach. Using the SEED subsystem, we discovered that the healthy rhizosphere maize plant was dominated by 24 functional categories, while the NCLB infected rhizosphere maize plant was dominated by 4 functional categories. Alpha diversity analysis showed no significant (p > 0.05) difference between the healthy and diseased maize rhizosphere. However, the analysis of beta diversity showed a significant difference. The substantial abundance of functional groups detected especially in LI indicates that presence of plant diseases altered the functions of soil microbiomes. The significant abundance of the unknown role of rhizosphere microbiomes in disease management suggests the presence of some undiscovered functional genes associated with the microbiome of the healthy maize rhizosphere. Hence, further investigation is needed to explore the roles of these functional genes for their agricultural or biotechnological relevance.